THE CUSTOMER PERCEPTION OF LOCAL GOLD JEWELRY RETAILER IN TRADITIONAL MARKET- PASAR 45 MANADO - Jalaham, Winda Angraini; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Gold jewelry is the one of complete package especially for women. Gold Jewelry is something that including of needs and wants. Hobby is specific with needs. Someone that has hobby to buy gold jewelry is someone that compels their action for their satisfaction. Others oppose gold jewelry is something that someone want. Lifestyle and self-esteem can make someone desired something in satisfaction. In business, perception of customers is important. The purpose of this study is to analyze the Customer Perception of Branded and Non-Branded Local Gold Jewelry Retailer in Traditional Market Pasar 45 Manado. The population observed was customers of jewelry in Manado City with using In-depth interview as many as 10 informants. This research is using qualitative method by using descriptive research that will describe the topic and explain the result of the interview. Interview result showed that most of customers are interested with non-branded products because non-branded products have many kind of model variant, price is affordable, and appropriate for all society. In traditional market, promotion should be a further enhanced. However, promotion of product quality and product design that they have, should be able to show that the product is can compete with branded products. Keywords: customer perception, promotion, jewelry